Construction bid model for residential building projects in Dubai - Al Janabi, Tamadhur H. F. (2018)
Many construction firms face hardships during the economic crisis due to inaccurate bidding and difficulty in obtaining new projects because of cost fluctuation. The best option for construction firms during an economic crisis is to control their construction bid costs that fit the situation. The bidding cost during the economic crisis has led to losses in the execution of projects. The study investigated how the construction sector of Dubai, United Arab Emirate, experienced poor bidding performance during the economic crisis. This is evident when material cost was fluctuating and the construction companies had a tough time getting new projects due to inaccurate bidding. This research looked into the details of construction bidding management during the bidding stage by developing a construction bid mathematical model to assist construction firms avoid bidding problems during the economic crisis. Using the data gathered from the year 2009 and 2010 economic crash, a construction bid mathematical model and bidding plan methodology were developed to better prepare construction companies during economic crisis. The chronology of this study was divided into two phases. Phase one involved conducting an extensive literature review and collecting secondary data. Phase two focused on primary data gathering and analysis of the data collected. Documentary analysis and questionnaire surveys were engaged as a source and tool to gather the data. Data were analyzed using coefficient of variation and severity index. From the available data, the bid mathematical model for bidding was successfully developed. Then, ten experts validated this model and the data were analyzed whereby the results showed that the model has successfully reduced the estimation inaccuracy as well as predicted the problem faced especially bidding during the economic crisis. The findings have shown that it is very important to have a crisis-response plan in place to eradicate risks, secure the market and provide solutions to problems faced during the crisis. In conclusion, the model can be used to minimize the adverse effects on the construction companies, including the projects and stakeholders in the construction industry.